Agroecological characterization of Sacha Inchi (Plukenetia volubilis Linneo) crop production system in Arauquita, Colombia - Bohórquez-Rivera, Víctor; Cancino-Susan, Elsa; Quevedo-García, Enrique (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The Sacha Inchi or Inca peanut (Plukenetia volubilis Linneo) is an oily plant native to the Amazon, consumed by indigenous people since ancient times and recognized for its great contribution of essential fatty acids, antioxidants and proteins, being potentially attractive as a legal agricultural alternative for the reincorporation of insurgent groups. The objective of the research was to characterize the productive system of Sacha Inchi in the municipality of Arauquita, Colombia. Fifty farmers were selected (40 peasants and 10 ex-combatants of the FARC-EP), using an intentional non-probabilistic sampling. The information was collected through a questionnaire and two participatory workshops aimed at identifying limitations and potentialities of the agroecological and productive system. Data were analyzed using descriptive and multivariate statistics. The classification analysis allowed partitioning the set of farmers, based on socioeconomic and environmental characteristics necessary to guide extension plans. The results showed that the most used agroecological practices are: soil conservation, application of lime, use of compost as fertilizer, use of certified seed and direct sowing. Low crop rotation and limited use of phytosanitary products were evidenced. The participatory workshops made it possible to identify crop limitations such as low productivity, few marketing channels and lack of knowledge of some agroecological techniques necessary to improve its productivity. Agroecological practices must be reinforced and expanded through extension programs to achieve recognition as agroecological producers, since this crop is a highly viable alternative for the municipality of Arauquita, within the framework of the peace agreement.